Contribution of iron silicide nanoparticles to the magnetic behavior of annealed Fe‐implanted 6H‐SiC. Issue 1 (29th October 2014) - Diallo, M. L.; Fnidiki, A.; Viret, M.; Drouet, M.; Eyidi, D.; Declémy, A.
Abstract The Fe‐implanted SiC is an interesting system in the DMS field although ion implantation induces strong microstructural defects needing post‐implantation treatments for recovery. These post‐implantation treatments often induce the formation of parasitic magnetic secondary phases. In this work, using XRD, SEM, TEM, CEMS and SQUID it is shown that post‐annealing of Fe‐implanted 6H‐SiC at 380°C with a few 1016Fe+ ions/cm2 at 900°C/60min, 1000°C/85min and 1300°C/4min enhanced the ferromagnetic ordering which can be partially explained by the formation of iron rich superparamagnetic nanoparticles. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)